To Compare the Clinical Assessment of Spinal Anaesthesia with Levobupivacaine Alone Vs A Combination of Levobupivacaine and Dexmedetomidine - P Pradeep; Sachin D Joshi; Uma Maheshwara Rao W (Academia Anesthesiologica International, 2018)
Background: Spinal anaesthesia is a commonly used method that offers rapid initiation of action along with efficient and evenly spread numbing of both sensory and motor functions. Levobupivacaine is a favourable substitute for spinal anaesthesia since it has less cardiovascular and central nervous system effects. When administered intrathecally, dexmedetomidine is linked to a longer duration of motor and sensory block, stable hemodynamics, and reduced need for further pain relief within a 24-hour period. Aim: To compared the clinical assessment of spinal anaesthesia with Levobupivacaine alone vs a combination of Levobupivacaine and Dexmedetomidine. Subjects and Methods: A total of 160 patients, classified as American Society of Anesthesiologists physical status I or II, were included in this randomised, double-blind trial. The patients were of both sexes, aged between 20 to 60 years, with a body weight ranging from 35 to 70 kg and a height more than 150 cm. The groups were partitioned and therapy was administered in the following manner: Control Group (Group-A, N=80): 0.5% Isobaric levobupivacaine 15 mg (3 ml) mixed with 0.3 ml normal saline; Study Group (Group-B, N=80): 0.5% Isobaric levobupivacaine 15 mg (3 ml) mixed with 0.3 ml (3 μg) dexmedetomidine. The motor block is assessed using the modified Bromage score. Results: In Group A, the average time it took for the sensory block to reach the T10 dermatome was 9.01 ± 0.88 minutes, whereas in Group B it was 5.57 ± 0.78 minutes (P=0.03). In group A, the median maximum sensory level reached was at the T6 dermatome, taking an average of 18.11 ± 1.64 minutes. In group B, the median maximum sensory level was at the T4 dermatome, attained in an average of 10.21 ± 1.34 minutes (P=0.001). In Group A, the average length of sensory block (time until regression to S1 dermatome) was 209.99 ± 7.85 min, but in Group B it was 349.88 ± 7.63 min (P = 0.001). The differences between the two groups were statistically highly significant. The average duration required to reach maximal motor block was 13.99 ± 1.24 minutes for group A and 9.14 ± 0.88 minutes for Group B (P=0.001). In addition, the average duration of motor block in Group A was 139.82 ± 4.29 min, whereas in Group B it was 188.85 ± 5.85 min. Both differences exhibited a high level of significance (P = 0.001). 12.5% of patients in both Group A and Group B had hypotension, whereas 5% of patients in Group A and 15% of patients in Group B experienced bradycardia. However, these differences were not statistically significant (P > 0.05). Conclusion: The combination of levobupivacaine and dexmedetomidine has been determined to result in a sensory and motor block that starts earlier and lasts longer, as well as a longer period of postoperative pain relief compared to using levobupivacaine alone.